Legalisasi Aset Wakaf di Samarinda - Moh. Mahrus; Aulia Rachman; Muhammad Iqbal (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2019)
Legalization of Waqf Assets in Samarinda is an attempt to find out the concept of safeguarding waqf property in national legal representation which is manifested in the reality of waqf property in Samarinda. This study uses qualitative approach. In the real term, the legalization effort is carried out by accurately documenting it, either in the form of a waqf pledge deed, replacement deed or in the form of a waqf land certificate. The efforts to realize the legal status of waqf assets are a form of realization of benefit. Actually, this becomes the task of managements gather with other relevant agencies, namely the Ministry of Religion, the Indonesian Waqf Board, and the National Land Agency. The strategy adopted is to register, administer, announce the existence of waqf property and monitor it. While the challenges faced when seeking the legality of waqf assets include a lack of awareness about the legal status of waqf in the community. Also the lack of human resources that needs to be improved in competence, as well as the number of managements that have not been registered at the Indonesian Waqf Board. Whereas the opportunity is the existence of established regulations related to waqf, starting from the registration of waqf assets, management, supervision and even productivity, namely Law Number 41 of 2004 concerning Waqf.